The association between aortic regurgitation and increased arterial wave reflection - Haroon Kamran; Louis Salciccioli; Carl-Frederic Bastien; Abhishek Sharma; Jason M. Lazar (Artery Research, 2011)
Background: Chronic Aortic Regurgitation (AR) increases left ventricular preload and afterload, which may enhance arterial wave reflection. The effects of AR on noninvasive measures of arterial wave reflection and central aortic pressure are unknown. Methods: To determine the relation between AR and wave reflection, we prospectively studied 86 subjects with AR and 50 controls referred for echocardiography. Peripheral (P) blood pressures (BP) were measured using an automated sphygmomanometer. Central aortic systolic (CS) BP, central pulse pressure (CPP), central augmented pressure (AP), heart rate corrected augmentation index (AI75), AI, reflected wave systolic duration (ΔTr) and round trip travel time (Tr) were derived from the radial artery waveform obtained by applanation tonometry (Sphygmocor®, Atcor Medical). Pulse pressure amplification (PPA) was calculated as peripheral PP/central PP. There were 50 controls, 50 with mild, 25 with moderate, and 11 subjects with severe AR. Clinical characteristics were similar among the groups. Results: AP, AI75, and CPP increased in a stepwise manner with increasing AR severity. On analysis of variance adjusted for age, gender, height, weight, mean peripheral BP, ejection fraction, and medication classes, AR severity was independently associated with increased AI75 (p<0.001), AP (p<0.001), CSBP (p=0.04). PPA decreased in a stepwise manner with increasing AR severity (p=0.001). Tr decreased and ΔTr increased. Conclusions: AR is associated with increased amplitude and duration and earlier onset of the reflected pressure wave, which suggests arterial wave reflection to be a potentially important consideration in patients with AR.